Attributes of tree species and their capability of carbon capture in the municipality of Querétaro, México - Soto-Correa, José Carmen; Cambrón-Sandoval, Víctor Hugo; Renaud-Rangel, Rebeca (Instituto de Ecología, A.C., 2019)
Attributes of the shrub and tree species components of the tropical deciduous forest within the Municipality of Querétaro, Querétaro are described. We used a random sampling of 36 sites of natural vegetation with exclusion criteria. Sites were delimited to a 25 m × 25 m quadrant. Within the quadrant, the species of all individuals of the tree and shrub species greater than 150 cm were identified, not taking into account the Cactaceae and Succulents. Measurements were made of the trees: basal diameter, diameter at breast height, total tree height, canopy height and diameter; carbon capture by species was estimated taking into account the climatic site variables, where they grow. Twenty-two species of shrubs and trees were observed, with Acacia schaffneri, Bursera fagaroides, Forestiera phillyreoides, Karwinskia humboldtiana, Dodonaea viscosa and Ipomea murucoides being the most abundant, while the ones with the highest carbon content are species such as: Prosopis laevigata and Leucaena leucocephala and the less abundant were Randia thurberi and Erytrina coralloides. These results are indispensable for developing and designing proposals for reforestation and conservation of the tropical deciduous forest.